Cyclical Patterns Affect Microbial Dynamics in the Water Basin of a Nuclear Research Reactor - Van Eesbeeck, Valérie; Props, Ruben; Mysara, Mohamed; Petit, Pauline C. M.; Rivasseau, Corinne; Armengaud, Jean; Monsieurs, Pieter; Mahillon, Jacques; Leys, Natalie (Frontiers in Microbiology, 2021)
The BR2 nuclear research reactor runs in successive phases of operation (cycle) and shutdown, whereby a water basin surrounding the reactor vessel undergoes periodic changes in physico-chemical parameters such as flow rate, temperature and radiation. The aim of this pioneering study is to explore the microbial community in this unique environment and to investigate its long-term dynamics using a 16S rRNA amplicon sequencing approach. Results from two sampling campaigns spanning several months showed a clear shift in community profiles: cycles were mostly dominated by two OTUs assigned to an unclassified Gammaproteobacterium and Pelomonas, whereas shutdowns were dominated by an OTU assigned to Methylobacterium. Although one year apart, both campaigns showed similar results, indicating that the system remained stable over this two-year period. The community shifts were linked with changes in flow rate, temperature and radiation by NMDS and correlation analyses. In addition, radiation was proposed to cause a decrease in cell number, whereas temperature had the opposite effect. Chemoautotrophic use of H2 and dead cell recycling are proposed to be used as a strategies for nutrient retrieval in this extremely oligotrophic environment.